Effect of age on the physicochemical quality of pork and fresh-style sausages from gilts and culled sows - Dutra, Daniel Rodrigues [UNESP]; Dias, Ana Veronica Lino [UNESP]; Villegas-Cayllahua, Erick Alonso [UNESP]; Pereira, Mateus Roberto [UNESP]; Cavalcanti, Érika Nayara Freire [UNESP]; Domenici, Thamiris Daiane [UNESP]; Lima, Igor Correia [UNESP]; de Mattos Machado, Leticia [UNESP]; de Souza, Isabella da Luz [UNESP]; Giampietro-Ganeco, Aline [UNESP]; de Oliveira, Rodrigo Fortunato [UNESP]; de Fidelis, Heloisa Almeida [UNESP]; et al. (Elsevier, 2025)
The increasing need to optimize the utilization of meat from culled sows in the pork industry has raised interest in understanding how animal age and physiological status affect product quality. Therefore, this study aimed to assess the impact of age and physiological status (culled sows vs. replacement gilts) on the physicochemical quality of pork and fresh-style sausages. Samples from 30 female pigs (15 gilts aged 5–6 months and 15 sows culled after seven parities, ~3.5 years), all from the same genetic background (Large White × Landrace), were analyzed using a completely randomized design. The Longissimus thoracis et lumborum muscle was evaluated for marbling, pH, color, water-holding capacity, cooking loss, shear force, texture profile analysis (TPA), lipid oxidation (TBARs), chemical composition, collagen, cholesterol, sarcomere length, total heme pigments, and myofibrillar fragmentation index (MFI). Meat from sows exhibited significantly higher (p < 0.05) pH, redness (a*), heme pigments, marbling, cohesiveness, gumminess, chewiness, and MFI, along with lower lipid and cholesterol contents. Sausages from sow meat showed higher pH, a*, moisture, ash content, and firmer texture, while those from gilts presented higher lightness (L*), yellowness (b*), fat content, and TBARs, indicating greater lipid oxidation. Despite processing, sausages retained textural characteristics derived from the original meat. Although sow meat was tougher and darker, its favorable protein and fat profile supports its suitability for value-added meat products. These findings highlight the importance of considering age and physiological status when selecting raw materials for pork processing and product development.